The Genomics of Isolated Populations of Gampsocleis glabra (Orthoptera: Tettigoniidae) in Central and Western Europe - Oliver Hawlitschek; Carsten Bruns; Lara-Sophie Dey; Soňa Nuhlíčková; Rob Felix; Hein van Kleef; Jacqueline Nakel; Martin Husemann (Insects, 2023)
Habitat destruction and fragmentation are among the major current threats to global biodiversity. Fragmentation may also affect species with good dispersal abilities. We study the heath bushcricket Gampsocleis glabra, a specialist of steppe-like habitats across Europe that are highly fragmented, investigating if these isolated populations can be distinguished using population genomics and if there are any traces of admixture or dispersal among them. We try to answer these questions using genome-wide SNP data generated with ddRAD sequencing. We calculated F-statistics and visualized differentiation using STRUCTURE plots. While limited by the difficulty of sampling this threatened species, our results show that all populations except one that was represented by a singleton were clearly distinct, with pairwise FST values between 0.010 and 0.181. STRUCTURE indicated limited but visible admixture across most populations and probably also an exchange of individuals between populations of Germany and The Netherlands. We conclude that in G. glabra, a certain amount of gene flow has persisted, at least in the past, also among populations that are isolated today. We also detect a possibly more recent dispersal event between a population in The Netherlands and one in Germany, which may be human aided. We suggest that the conservation of larger populations should be maintained, that efforts should be taken to restore abandoned habitat, that the preservation even of small habitat fragments may be beneficial for the conservation of this species, and that these habitats should be regularly monitored for possible (re-)colonization.